Agro by-Product Fermentation Product as Poultry Feedstuffs - Pasaribu, Tiurma (Indonesian Bulletin of Animal and Veterinary Sciences, 2007)
Feed is the main component in livestock industry, and contributes 70% of the total farming cost. Agriculture by-product is one of the alternative feed ingredients for poultry feed, but unfortunately they have low in nutritive value and high fiber contents that inhibit metabolism process. Fermentation technology is one of the methods to improve the nutritive value and to decrease fiber content of agriculture by-product. This paper explains the process of technology fermentation process and the effect of fermented product on poultry. Fermented agriculture by-product can be offered 5 to 30% depend on substrates and species of poultry without causing death. Fermentation process is not difficult to do, therefore agriculture by-product fermentated product are potential as poultry feedstuffs. Â  Key words: Agriculture by-product, technology of fermentation, fermented products, poultry